Reconstructing reactivity in dynamic host–guest systems at atomistic resolution: amide hydrolysis under confinement in the cavity of a coordination cage. Issue 37 (15th September 2022) - Delle Piane, Massimo; Pesce, Luca; Cioni, Matteo; Pavan, Giovanni M.
Abstract : Encapsulation of guests in metal–organic cages allows control over chemical reactivity. Focusing on the hydrolysis of amides, here we show an effective molecular simulation approach to reconstruct reactivity in host–guest systems in dynamic regimes. Abstract : Spatial confinement is widely employed by nature to attain unique efficiency in controlling chemical reactions. Notable examples are enzymes, which selectively bind reactants and exquisitely regulate their conversion into products. In an attempt to mimic natural catalytic systems, supramolecular metal–organic cages capable of encapsulating guests in their cavity and of controlling/accelerating chemical reactions under confinement are attracting increasing interest. However, the complex nature of these systems, where reactants/products continuously exchange in-and-out of the host, makes it often difficult to elucidate the factors controlling the reactivity in dynamic regimes. As a case study, here we focus on a coordination cage that can encapsulate amide guests and enhance their hydrolysis by favoring their mechanical twisting towards reactive molecular configurations under confinement. We designed an advanced multiscale simulation approach that allows us to reconstruct the reactivity in such host–guest systems in dynamic regimes. In this way, we can characterize amide encapsulation/expulsion in/out of the cage cavity (thermodynamics and kinetics), coupling such host–guest dynamic equilibrium with characteristic hydrolysis reaction constants. All computed kinetic/thermodynamic data are then combined, obtaining a statistical estimation of reaction acceleration in the host–guest system that is found in optimal agreement with the available experimental trends. This shows how, to understand the key factors controlling accelerations/variations in the reaction under confinement, it is necessary to take into account all dynamic processes that occur as intimately entangled in such host–guest systems. This also provides us with a flexible computational framework, useful to build structure–dynamics–property relationships for a variety of reactive host–guest systems.